2015
DOI: 10.3747/co.22.2562
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Landscape of Brachytherapy for Cervical Cancer: A Canadian Practice Survey

Abstract: Background We documented changes in practice from 2009 to 2012 for cervical cancer brachytherapy in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This department has an MRI scanner in the radiotherapy centre. Use and expansion of soft tissue imaging throughout Australia and New Zealand compares favourably to other parts of the world, with uptake exceeding most other countries and regions, Table . The most notable increase in soft tissue imaging has been in the use of ultrasound to aid applicator insertion (86%) and treatment planning (29%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This department has an MRI scanner in the radiotherapy centre. Use and expansion of soft tissue imaging throughout Australia and New Zealand compares favourably to other parts of the world, with uptake exceeding most other countries and regions, Table . The most notable increase in soft tissue imaging has been in the use of ultrasound to aid applicator insertion (86%) and treatment planning (29%).…”
Section: Discussionmentioning
confidence: 99%
“…Use and expansion of soft tissue imaging throughout Australia and New Zealand compares favourably to other parts of the world, with uptake exceeding most other countries and regions, Table 3. 17,[21][22][23][24][25][26][27] The most notable increase in soft tissue imaging has been in the use of ultrasound to aid applicator insertion (86%) and treatment planning (29%). While many practitioners have reported on the utility of using ultrasound for difficult insertions, Small et al recommend using ultrasound for all insertions as they felt uterine perforation was possible in any patient.…”
Section: Imagingmentioning
confidence: 99%
“…The fast developments of image-guided adaptive treatment of LACC induces changing 'Patterns of care' [14][15][16][17][18]. The importance of training, audits, and continuous education is widely recognized, and sharing experiences (joys and pitfalls) for chosen approaches can boost clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Among the therapeutic options, recent studies have indicated that intracavitary brachytherapy (BT) has been shown to increase survival and local control of tumours in addition to external beam radiation therapy . BT is a type of treatment modality that evolved from 2D‐based dosimetry using point‐based dosing to 3D‐based volumetric planning . Volumetric planning, conducted before treatment, could increase the precision of radiation dose delivery by improving the tumour definition and adjacent normal tissues.…”
Section: Introductionmentioning
confidence: 99%